2013
DOI: 10.1039/c3nr00334e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of aqueous colloidal mesostructured and mesoporous silica nanoparticles with controlled particle size in a very wide range from 20 nm to 700 nm

Abstract: Particle size control of colloidal mesoporous silica nanoparticles (CMPS) in a very wide range is quite significant for the design of CMPS toward various applications, such as catalysis and drug delivery. Various types of CMPS and their precursors (colloidal mesostructured silica nanoparticles (CMSS)) with different particle sizes (ca. 20-700 nm) were newly prepared from tetraalkoxysilanes with different alkoxy groups (Si(OR)4, R = Me, Et, Pr, and Bu) in the presence of alcohols (R'OH, R' = Me, Et, Pr, and Bu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 72 publications
(119 reference statements)
4
62
0
Order By: Relevance
“…Significant weight loss occurred between 250 and 500 °C and this is due to removal of pyridinium ILs templates (Fig. S3) [19,40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant weight loss occurred between 250 and 500 °C and this is due to removal of pyridinium ILs templates (Fig. S3) [19,40].…”
Section: Resultsmentioning
confidence: 99%
“…TG curves (Fig. S2) shows significant weight loss occurred between 250 and 500 °C which due the removal pyridinium ILs templates [19,40]. The porosity of the synthesized MNSs was further examined by N 2 adsorption-desorption and all MNSs sample exhibit type IV isotherm which is the norm for mesoporous materials (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34]. Additionally, alcohols with long alkyl chains have been shown to affect MSN particle size by altering the tetraalkylsilicate hydrolysis kinetics [35]. The ratio of silica precursor to surfactant is also crucial for soft templated MSN, with ratios lower than 0.13 preventing the pores from extending through the entire particle [36].…”
Section: Mesoporous Silica Nanoparticles: Ideal Candidates For Proteimentioning
confidence: 99%
“…116,117 We also investigated the effect of alcohols on the size control of colloidal MSNs, and found that the addition of a hydrophobic alcohol leads to the enlargement of MSNs (Figure 11). 118 These methods are very useful for the precise control of the diameter of MSNs because only the hydrolysis rate can be tuned without drastically changing the condensation rate.…”
Section: Relationship Between Preparative Conditions Of Colloidal Msnmentioning
confidence: 99%